Resolution of labor conflicts: case of negotiation of a collective contract in Codelco (Chile) - Cea Rodríguez, Jorge; Riveros Sudy, Jorge; Cárdenas Gutiérrez, Roberto (Estudios de Administración, 2019)
Codelco, the world’s leading producer of copper, is a state-owned enterprise, leader in planetary reserves of ore and one of the engines behind Chile’s development. It is dedicated to exploring mining resources, processing them to produce refined copper and by-products, and then marketing them to customers worldwide. The main market is Asia, followed by Europe and South America. This work is done through its eight mining divisions. The case examines the resolution of a labor conflict arising between the Codelco mineral company (in the mining division of Chuquicamata) and the worker’s union in a collective bargaining process. The collective bargaining process had different stages, from the first offer given by the “Offer Early Signing” company, through the process of “Mediation of Good Offices”, the beginning of the legal strike and the last negotiations until finally achieving the end of the legal strike and agreement between the parties. The agreement of the unions with the company’s “Improved Final Offer” meant that after agreeing to a bonus for the end of conflict of 14.1 million pesos and a salary readjustment of 1.2 percent, the workers had to return to their jobs. The next collective bargaining would be in 3 years. A contextualization and description of the collective bargaining process is carried out based on published journalistic information about the case and some scientific sources. At the end a series of questions are raised to generate a discussion in a Human Resource Management class.